1987
DOI: 10.1111/j.1439-0396.1987.tb00032.x
|View full text |Cite
|
Sign up to set email alerts
|

Einfluß von Protein‐ und Energierestriktion sowie Realimentation auf den Gehalt an Wachstumshormon im Serum wachsender Ratten

Abstract: Zusammenfassung Um den Einfluß von leichtem, definiertem Energie‐ und/oder Proteinmangel sowie einer anschließenden Realimentation auf Wachstum und Serum‐GH‐Gehalt zu untersuchen, wurden zwei Versuche mit entwöhnten Sprague‐Dawley Ratten in jeweils 4 Fütterungsgruppen I (EnPn), II (EnPl), III (ElPn) und IV (ElPl) durchgeführt. Im 1. Versuch wurden 32 männliche und 32 weibliche Ratten über einen Zeitraum von 30 Tagen unterschiedlich mit umsetzbarer Energie (En = 16 kJ, El = 13 kJ pro kg Diät) und mit Rohprotein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
1997
1997

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…This means that the reduced GH concentrations in the serum of the Zn-deficient and the pair-fed control rats is the result of the reduced feed intake and the associated protein and energy depletion rather than being caused by Zn deficiency per se. Other authors also reported a marked influence of feed intake {Phillips and Young 1976; Ghavami-Maibodi, Collipp, Castro-Magana, Stewart and Chen 1983;Nishi, Hatano, Aihara, Fujie and Kihara 1989) or of energy and protein deficiency (Kirchgefiner, Jacob-Hammermann and Roth 1987;Jacob-Hammermann, Kirchgefiner and Roth 1987) on the GH concentration in the serum. In situations of marginal Zn depletion, when the rats' feed intake was unaffected or only slightly impaired (Kirchgefiner and Roth 1985), while the serum Zn concentrations were nonetheless significantly reduced, GH concentrations in the serum of the Zn-deficient rats were also distinctly reduced compared to the pair-fed control rats.…”
Section: Introductionmentioning
confidence: 93%
“…This means that the reduced GH concentrations in the serum of the Zn-deficient and the pair-fed control rats is the result of the reduced feed intake and the associated protein and energy depletion rather than being caused by Zn deficiency per se. Other authors also reported a marked influence of feed intake {Phillips and Young 1976; Ghavami-Maibodi, Collipp, Castro-Magana, Stewart and Chen 1983;Nishi, Hatano, Aihara, Fujie and Kihara 1989) or of energy and protein deficiency (Kirchgefiner, Jacob-Hammermann and Roth 1987;Jacob-Hammermann, Kirchgefiner and Roth 1987) on the GH concentration in the serum. In situations of marginal Zn depletion, when the rats' feed intake was unaffected or only slightly impaired (Kirchgefiner and Roth 1985), while the serum Zn concentrations were nonetheless significantly reduced, GH concentrations in the serum of the Zn-deficient rats were also distinctly reduced compared to the pair-fed control rats.…”
Section: Introductionmentioning
confidence: 93%